Labor-market Frictions, Incomplete Insurance and Severance Payments - Étienne Lalé (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We analyze the effects of government-mandated severance payments in a rich life-cycle model with search-matching frictions in the labor market, risk-averse agents and imperfect insurance against idiosyncratic shocks. Our model emphasizes a tension between workerfirm wage bargains and consumption smoothing: entry wages respond to expected future severance payments by tilting downwards, which runs counter to having a smooth consumption path. Quantitatively, we find that these wage-shifting effects are sizable enough for severance payments to produce large welfare losses. Our assessment contrasts sharply with previous studies that restricted the extent of worker-firm bargaining to analyze the welfare implications of severance payments.
Keywords: 330